PENGARUH DISEMINASI PERPAJAKAN DAN MUTU LAYANAN TAX TERHADAP KINERJA PELAYANAN KANTOR PELAYANAN PAJAK DENGAN KEPATUHAN WAJIB PAJAK SEBAGAI VARIABEL INTERVENING - Uswatun Chasanah; Yunita Fitri Wahyuningtyas; Syaifullah Chairman Olways Affandi (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2023)
This research discusses the effect of tax socialization and the quality of tax services on the service performance of the Small Tax Office (Kantor Pelayanan Pajak Pratama) with taxpayer compliance as an intervening variable. This research was conducted at Kantor Pelayanan Pajak (KPP) Pratama Yogyakarta. The population in this research were taxpayers registered at the KPP Pratama Yogyakarta before 2021, which recorded as much as 152,834. The number of samples in this research was calculated by Slovin formula and determined based on the purposive sampling method. The data used in this research is primary data obtained through an online questionnaire of 100 respondents. This research has been done through Structural Equation Model (SEM) with Partial Least Square (PLS) approach using SmartPLS ver. 3.3.3 for Windows software. The results of this research show that tax socialization has a positive and significant effect on taxpayer compliance and service performance. The quality of tax services also has a positive and significant effect on service performance but does not affect taxpayer compliance. Furthermore, as an intervening variable, taxpayer compliance is statistically qualified to mediate the effect of tax socialization on service performance but fails to mediate the effect of service quality on service performance.